2021
DOI: 10.1002/jcop.22668
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of psychological distress on the link between socio‐ecological factors and quality of life of Filipino adults during COVID‐19 crisis

Abstract: Anchored on the Ecological Systems Theory, this study aimed to determine how psychological distress operates as an underlying mechanism in the impact of socio‐ecological factors on the quality of life of Filipino adults during coronavirus disease 2019 (COVID‐19) crisis. A cross‐sectional online survey was conducted to assess perceptions of 401 adults on socio‐ecological factors (i.e., safety at home, trust in public institutions, and financial difficulties), psychological distress, and quality of life during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
(94 reference statements)
2
25
0
Order By: Relevance
“…Several individuals lost their jobs or received pay cuts, while others faced job uncertainty or could not find employment. Since financial difficulties due to the pandemic were linked to greater psychological distress (Aruta et al, 2021), the importance of financial satisfaction observed here aligns not only with previous research, but with the current economic situation too.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several individuals lost their jobs or received pay cuts, while others faced job uncertainty or could not find employment. Since financial difficulties due to the pandemic were linked to greater psychological distress (Aruta et al, 2021), the importance of financial satisfaction observed here aligns not only with previous research, but with the current economic situation too.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, higher financial satisfaction is consistently strongly correlated with higher SWB, in both worldwide samples (Ng & Diener, 2014 ) and a Singaporean sample (Ng et al, 2019 ). Additionally, financial difficulties in the family due to the pandemic were found to be associated with greater psychological distress and lower quality of life among Filipino adults (Aruta et al, 2021 ). Financial difficulties also predicted lower life satisfaction and flourishing, and more symptoms of depression and anxiety among Filipino students during the pandemic (Galanza et al, 2021 ).…”
Section: Predictors Of Well‐beingmentioning
confidence: 99%
“…We used the SEM in step 3 to cross-validate the hypothesised model (see Figure 2 ). The mediating effects of SC on the associations between PA and QoL and the predictive effects of parent proxy-report QoL on self-report QoL were examined using 5,000 bootstrap samples, as 5,000 bootstrap samples are frequently used ( 37 ). A bias-corrected and accelerated 95% confidence interval (CI) and a maximum likelihood estimation method for missing data were used in the data analysis ( 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 pandemic has caused radical changes to the average Filipino’s life, such as loss of income and decreased social interaction due to the mitigating interventions implemented by the government [ 10 , 11 ]. Further psychosocial distress is likely to impact those directly affected by COVID-19 by either contracting the disease or having to take care of a family member who has been infected with COVID-19.…”
Section: Introductionmentioning
confidence: 99%